New Insights into the Pathogenesis of Alcohol-Induced ER Stress and Liver Diseases - Cheng Ji (International Journal of Hepatology)
Alcohol-induced liver disease increasingly contributes to human mortality worldwide. Alcohol-induced endoplasmic reticulum (ER) stress and disruption of cellular protein homeostasis have recently been established as a significant mechanism contributing to liver diseases. The alcohol-induced ER stress occurs not only in cultured hepatocytes but also  in vivo  in the livers of several species including mouse, rat, minipigs, zebrafish, and humans. Identified causes for the ER stress include acetaldehyde, oxidative stress, impaired one carbon metabolism, toxic lipid species, insulin resistance, disrupted calcium homeostasis, and aberrant epigenetic modifications. Importance of each of the causes in alcohol-induced liver injury depends on doses, duration and patterns of alcohol exposure, genetic disposition, environmental factors, cross-talks with other pathogenic pathways, and stages of liver disease. The ER stress may occur more or less all the time during alcohol consumption, which interferes with hepatic protein homeostasis, proliferation, and cell cycle progression promoting development of advanced liver diseases. Emerging evidence indicates that long-term alcohol consumption and ER stress may directly be involved in hepatocellular carcinogenesis (HCC). Dissecting ER stress signaling pathways leading to tumorigenesis will uncover potential therapeutic targets for intervention and treatment of human alcoholics with liver cancer.